Keberadaan Wali Dalam Akad Nikah - Simamora, Harapan; Hutasuhut, Mitsaqo Gholizho; Ramadani, Mawar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The existence of a guardian in a marriage contract is a fundamental issue in Islamic law. This article discusses the concept of guardian as one of the pillars of marriage based on the views of the Shafi'i and Hanafi schools and its relevance to positive law in Indonesia. This research uses a normative juridical approach with comparative analysis methods. The research results show that according to the Syafi'i school of thought, a guardian is an obligatory pillar in a marriage, so that without a guardian, the marriage contract is considered invalid. In contrast, the Hanafi school views guardianship as an additional requirement, not a rukun, so that adult women can marry themselves. The Compilation of Islamic Law in Indonesia is more inclined towards the views of the Shafi'i school, which emphasizes the importance of the presence of a guardian in marriage. It is hoped that this article will provide a deeper understanding of the role of guardians in Islamic law and its application in the context of Indonesian society.